Status and prospects of biotechnology applications to conservation, propagation and genetic improvement of yam - Balogun, M.; Gueye, B. (CRC Press, 2013)
Yam plays a critical role in providing good quantity and quality yield and source of income to combat the challenge of food insecurity in the tropics. Although significant advances in science and technology have improved efficient management and improvement of their genetic resources, the mission of fully exploiting their potentials is yet to be maximally achieved. Lack of formal seed systems increases germplasm losses and reduces yields. Research is needed in the control of tuber dormancy in yam. Biotechnological approaches, especially in vitro culture of meristem/shoot tip combined with thermo/cryotherapy are promising methods to clean yam seeds of pathogens like viruses. The multiplication of clean yam seeds so obtained can be propagatedusing improved systems such as temporary immersion bioreactors, aeroponics and photoautotrophic systems but knowledge gaps still exist on their use. Although the relative importance of clean materials, survival on farmers’ fields, production cost and multiplication ratio should be determined and considered in deciding the propagation technique to adopt, conventional and improved tissue culture techniques will be indispensable in the production of clean seed yams. Marker-assisted selection, embryo culture, genetic transformation and genome sequencing have been initiated to support conventional genetic improvement, but investigations into the presence of transposable elements, site targeted mutagenesis, somatic embryogenesis and haploid plant production will be necessary to fast track the genetic improvement. These biotechnological approaches will not only enhance the use of disease-free, quality-declared planting materials but also facilitate germplasm exchange and speed up genetic improvement while providing excellent means for conservation.